Development and Evaluation of Chromosome Segment Substitution Lines Carrying Overlapping Chromosome Segments of the Whole Wild Rice Genome - Yang, Dewei; Ye, Xinfu; Zheng, Xianghua; Cheng, Chaoping; Ye, Ning; Huang, Fenghuang (Frontiers in Plant Science, 2016)
Common wild rice (Oryza rufipogon Griff.) represents an important resource for rice improvement. Genetic populations provide the basis for a wide range of genetic and genomic studies. In particular, chromosome segment substitution lines (CSSLs) are most powerful tools for the detection and precise mapping of quantitative trait loci (QTLs). In this study, 146 CSSLs were produced; they were derived from the crossing and back-crossing of two rice cultivars: Dongnanihui 810 (Oryza sativa L.), an Indica rice cultivar as the recipient, and ZhangPu wild rice, a wild rice cultivar as the donor. First, a physical map of the 146 CSSLs was constructed using 149 molecular markers. Based on this map, the total size of the 147 substituted segments in the population was 1145.65 Mb, or 3.04 times that of the rice genome. To further facilitate gene mapping, heterozygous chromosome segment substitution lines (HCSSLs) were also produced, which were heterozygous in the target regions. Second, a physical map of the 244 HCSSLs was produced using 149 molecular markers. Based on this map, the total length of substituted segments in the HCSSLs was 1683.75 Mb, or 4.47 times the total length of the rice genome. Third, using the 146 CSSLs, two QTLs for plant height, and one major QTL for apiculus coloration were identified. Using the two populations of HCSSLs, the qPa-6-2 gene was precisely mapped to an 88 kb region. These CSSLs and HCSSLs may, therefore, provide powerful tools for future whole genome large-scale gene discovery in wild rice, providing a foundation enabling the development of new rice varieties. This research will also facilitate fine mapping and cloning of quantitative trait genes, providing for the development of superior rice varieties.